A biographical sketch of the Rev. K.M. Banerjea - Ghosha, Ramachandra (Calcutta : Progressive Publishers, 1980)
On Krishna Mohan Banerjea, 1813-1885, Indian Missionery, scholar, and patriot
Reprint. Originally published: 1893
Reprint of: Calcutta: Printed at the Samya Press, 1893; includes reproduction of the original t.p
Bibliography: p. xv
Keywords: Banerjea, Krishna Mohan, -- 1813-1885; Church of England -- India -- Clergy -- Biography; Converts from Hinduism -- Biography